Measurements and molecular interactions for N,N-dimethylformamide with ionic liquid mixed solvents - Attri, Pankaj; Reddy, P. Madhusudan; Venkatesu, P.; Kumar, Anil; Hofman, T. (Journal of Physical Chemistry B, 2010)
To understand the molecular interactions between N,N-dimethylformamide (DMF) with two families of ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (a) over the whole composition range at 25 degrees C under atmospheric pressure. The excess molar volume (V(E)) and the deviation in isentropic compressibilities (Delta K(s)) were predicted using these properties as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included two families of ILs such as ammonium salts and imidazolium salts. Diethylammonium acetate ([Et(2)NH][CH(3)COO], DEAA), triethylammonium actetate ([Et(3)NH][CH(3)COO], TEAA), triethylammonium dihydogen phosphate ([Et(3)NH][H(2)PO(4)], TEAP), and triethylammonium sulfate ([Et(3)NH][HSO(4)], TEAS) are ammonium salts and l-benzy1-3-methylimidazolium chloride (Bmiml[Cl]) belongs to the imidazolium family. The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion dipole, ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.